Teaching race struggles, strategies, and scholarship for the mass communication classroom - Daniels, George L.; Blom, Robin (Master class (Association for Education in Journalism and Mass Communication), 2021)
"When teaching about race, instructors from various backgrounds must acknowledge the challenges surrounding the topic while facilitating the learning of undergraduate and graduate students. This guide presents wisdom from the frontlines of teaching to help all instructors engage more fully and effectively with contentious topics"--